2018
DOI: 10.1371/journal.pone.0206137
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic extracellular matrix coatings improve the chronic biocompatibility of microfabricated subdural microelectrode arrays

Abstract: Intracranial electrodes are a vital component of implantable neurodevices, both for acute diagnostics and chronic treatment with open and closed-loop neuromodulation. Their performance is hampered by acute implantation trauma and chronic inflammation in response to implanted materials and mechanical mismatch between stiff synthetic electrodes and pulsating, natural soft host neural tissue. Flexible electronics based on thin polymer films patterned with microscale conductive features can help alleviate the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Increased thickness of the dural membrane and fibrous encapsulation of the electrode array that were found in this study have been widely reported in other chronic ECoG implantation studies for both epidural and subdural placement [23][24][25][26]. We further quantitatively measured the thickness of the reactive tissues in the subdural space and found statistically significant differences compared with the control dural membrane.…”
Section: Biocompatibilitysupporting
confidence: 81%
See 1 more Smart Citation
“…Increased thickness of the dural membrane and fibrous encapsulation of the electrode array that were found in this study have been widely reported in other chronic ECoG implantation studies for both epidural and subdural placement [23][24][25][26]. We further quantitatively measured the thickness of the reactive tissues in the subdural space and found statistically significant differences compared with the control dural membrane.…”
Section: Biocompatibilitysupporting
confidence: 81%
“…Several animal models have been established in preclinical research because of their relatively suitable skull sizes for implanted devices [ 23 , 24 , 26 , 39 , 40 , 41 , 42 ]. Minipigs and sheep have been used in studies of cuff electrodes and the WIMAGINE epidural ECoG system [ 25 , 43 ] to mimic the implantation of clinical devices.…”
Section: Discussionmentioning
confidence: 99%
“…The growing scientific interest in neural interfaces in the last decades is confirmed by the multitude of in vivo works focused on the testing of new and fully biocompatible coatings (Du et al, 2017; Spencer et al, 2017b; Shen et al, 2018; Vitale et al, 2018), less invasive implantation strategies (Tawakol et al, 2016; Shoffstall et al, 2018b) and new designs with improved electrical performance (Ferlauto et al, 2018; Xu et al, 2018) and with longer durability.…”
Section: Experimental Models To Study Foreign Body Response To Neuralmentioning
confidence: 99%
“…[52] Another study showed that coatings made of extracellular matrix (ECM) hydrogels, such as collagen and fibronectin, improve chronic biocompatibility of subdural ECoG arrays. [53] While coatings can improve the biocompatibility and signalto-noise ratio of a neuroimplantable device, neural foreign body response hinges more crucially on the form factor and material choices for a neuroimplantable device. Figure 2 summarizes the existing state of neuroimplantable devices, where each device is depicted with its target region in the brain, along with its form factor and materials choices.…”
Section: Materials Engineering As a Determinant Of Risk Factors And Fmentioning
confidence: 99%